A longitudinal evaluation of family caregivers' willingness to pay for an in-home nonpharmacologic intervention for people living with dementia: results from a randomized trial. (24th April 2021) - Jutkowitz, Eric; Pizzi, Laura T.; Popp, Jonah; Prioli, Katherine K.; Scerpella, Danny; Marx, Katherine; Samus, Quincy; Piersol, Catherine Verrier; Gitlin, Laura N.
Abstract: Objective: To determine the willingness-to-pay (WTP) of family caregivers to learn care strategies for persons living with dementia (PLwD). Design: Randomized clinical trial. Setting: Community-dwelling PLwD and their caregivers (dyads) in Maryland and Washington, DC. Participants: 250 dyads. Intervention: Tailored Activity Program (TAP) compared to attention control. TAP provides activities tailored to the PLwD and instructs caregivers in their use. Measurement: At baseline, 3 and 6 months, caregivers were asked their WTP per session for an 8-session 3-month in-home nonpharmacologic intervention to address behavioral symptoms and functional dependence. Results: At baseline, 3 and 6 months, caregivers assigned to TAP were willing to pay $26.10/session (95%CI:$20.42, $33.00), $28.70 (95%CI:$19.73, $39.30), and $22.79 (95%CI: $16.64, $30.09), respectively; attention control caregivers were willing to pay $37.90/session (95%CI: $27.10, $52.02), $30.92 (95%CI: $23.44, $40.94), $27.44 (95%CI: $20.82, $35.34), respectively. The difference in baseline to 3 and 6 months change in WTP between TAP and the attention control was $9.58 (95%CI: −$5.00, $25.47) and $7.15 (95%CI: −$5.72, $21.81). The difference between TAP and attention control in change in the proportion of caregivers willing to pay something from baseline to 3 and 6 months was −12% (95%CI: −28%, −5%) and −7% (95%CI:−25%, −11%), respectively. The difference in change in WTP, among caregivers willing to pay something, between TAP and attention control from baseline to 3 and 6 months was $17.93 (95%CI: $0.22, $38.30) and $11.81 (95%CI: −$2.57, $28.17). Conclusions: Family caregivers are willing to pay more for an intervention immediately following participation in a program similar to which they were asked to value.